(untitled) (Communications in Computational Physics, 2008)
The new potential model of interlayer intermolecular interaction was proposed to represent “ABAB” stacking of graphite. The bombardment of hydrogen atoms on the graphite surface was investigated using molecular dynamics simulation. Before the first graphene from the surface side was broken, the hydrogen atoms caused the following processes. In the case of the incident energy of 5 eV, many hydrogen atoms were adsorbed on the front of the first graphite. In the case of the incident energy of 15 eV, almost all hydrogen atoms were reflected by the first graphene. In the case of the incident energy of 30 eV, the hydrogen atoms were adsorbed between the first and second graphenes. The radial distribution function and the animation of the MD simulation demonstrated that the graphenes were peeled off one by one, which is called graphite peeling. One C2H2 was generated in such chemical sputtering. But the other yielded molecules often had chain structures terminated by the hydrogen atoms. The erosion yield increased linearly with time.